1984
DOI: 10.1252/jcej.17.120
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of bubble plume mixing by comparison with liquid jet mixing.

Abstract: Mixing of liquids in tanks by means of a non-reacting gas-bubble plume was studied by using a tracer response method. The circulation time was obtained from the period of a damping oscillation of the response curve. The mixing time was defined as the time required to reduce the concentration variation to within 1%of the mixed mean value and was measuredby an impulse response. The results indicate that the induced liquid flow-rate varies as the first power of the submergence depth of the nozzle and as the 1/3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Okita and Oyama (1963), cited in Maruyama et al (1982), describe the mixing time as a function of the jet Reynolds number and as the jet Froude number. Maruyama et al (1984) as well as Zughbi (2006) found that the jet location had a major influence on jet mixing. Fox and Gex (1956) as well as Zughbi and Rakib (2004) reported that the jet angle and the jet length influence mixing time.…”
Section: Review On Mixingmentioning
confidence: 96%
“…Okita and Oyama (1963), cited in Maruyama et al (1982), describe the mixing time as a function of the jet Reynolds number and as the jet Froude number. Maruyama et al (1984) as well as Zughbi (2006) found that the jet location had a major influence on jet mixing. Fox and Gex (1956) as well as Zughbi and Rakib (2004) reported that the jet angle and the jet length influence mixing time.…”
Section: Review On Mixingmentioning
confidence: 96%
“…Furthermore, the residence time distribution in the vessel is similar to that in a perfectly mixed vessel,deviations from it being dependent on the particular geometry of the vessel. Recent papers of Lane and Rice(1982)and Maruyama et al (1982Maruyama et al ( , 1984provided some relationships which can be used to calculate the mixing time in vessels in which liquid is mixed by turbulent jets. In the case of the smaller vessel (T= 0.2 m) the mixing times calculated from these relationships varied from 15 to 60s for the range of the flow parameters used in determination of the mass transfer coefficients.…”
Section: Mixing Characteristicsmentioning
confidence: 99%
“…Thus, the diameter to depth ratio nozzle, immersion depth of a lance, bath depth, and diameter to was 1.1, a value that is representative of a typical steel ladle. depth ratio [33][34][35][36][37][38]40]. In some studies, mixing experiments Nozzles enabling the introduction of various stirring gases were with various tracer input locations and positions of the meas-embedded in the bottom at a number of locations.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, mixing experiments Nozzles enabling the introduction of various stirring gases were with various tracer input locations and positions of the meas-embedded in the bottom at a number of locations. The tracer uring probe were also carried out [30,35,36]. used in this study was an aqueous sodium hydroxide solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation